Nivolumab plus ipilimumab induced endocrinopathy and acute interstitial nephritis in metastatic sarcomatoid renal-cell carcinoma: A case report and review of literature - Hino, Christopher; Nishino, Kevin; Pham, Bryan; Jeon, Won Jin; Nguyen, Michael; Cao, Huynh (Frontiers in Immunology, 2022)
The prognosis of sarcomatoid renal cell carcinoma has changed dramatically with the emergence of immune checkpoint inhibitors. Notably the use of nivolumab and ipilimumab combination therapy has demonstrated promising durable therapeutic response for patients with treatment-naïve sarcomatoid renal-cell carcinoma. We present a case of 45-year-old man with a history of metastatic sarcomatoid renal cell carcinoma treated with nivolumab plus ipilimumab who developed type 1 diabetes mellitus, adrenal insufficiency, thyroiditis/hypothyroidism, and acute interstitial nephritis as a result of immunotherapy.